Efficiency of Clinical Laboratories Affiliated Shiraz University of Medical Sciences in 2015: an Application of Data Envelopment Analysis - Taheri 1, Ali; Amin Shayan Jahromi 1*, Shapoor; Lotfi 2, Farhad (Shahroud Journal of Medical Sciences, 2017)
Background: Nowadays, healthcare systems are considered as important service sectors, and they are social development and welfare standards; hence the performance of this sector is highly important. Evaluating performance is the first step of various departments to determine the efficiency of the healthcare system. In the meantime, diagnostic laboratories of hospitals play important roles as specialized and technical units with a cost nature. So, far, the effectiveness of diagnostic laboratories has not been assessed in Iran, therefore, in this study, for the first time in Iran, the technical efficiency of laboratories covered by the Shiraz University of Medical Sciences (SUMS) was assessed in 2015. Methods: This cross-sectional study aimed to assess 10 selected laboratories from diagnostic laboratories in hospitals affiliated with SUMS. In this paper, data envelopment analysis (DEA), one of the most widely utilized methods, was used in determining performance. Results: Among the 10 examined laboratories affiliated by SUMS, 4 (40%) laboratories had increasing yield to the scale, and 6 (60%) laboratories had technical, managerial, and scale efficiency equal to one. Mean±SD of technical efficiency, managerial efficiency, and scale efficiency of examined laboratories were 92.4±16, 95.9±9, and 95.5±10, respectively. Conclusions: Studying the efficiency of the diagnostic laboratories affiliated with SUMS using DEA showed that most laboratories had a high level efficiency.